PENGARUH KURSI JAHIT ERGONOMIS TERHADAP PRODUKTIFITAS KERJA - Azriadi, Emon; Djumali, Denur; putra, Yudhy Soneta; Putra, Bary Dewanda (Jurnal Teknik Industri Terintegrasi (JUTIN), 2020)
This article explains the process of the chair design for the tailor with the case study of the tailors in the convection company that uses the Brother brand sewing machine with certain specifications. Research begins with interviews to know the complaints and needs of the tailor will be a means of chair work and also to get the way out so that tailor complaints can be reduced. In addition to interviews, also observations and measurements of the seats that are being used by the company as a comparator, collecting the sewing machine data used, conducting quotation position test to determine the tendency to sit the tailors. In addition, to obtain the main components, design, and dimensions of the Chair are also working observations and measurements anthropometry the tailors. From the analysis of the data that resulted in the design of the chair, then made a prototype that is expected to suit the needs of tailor in the convection company.